Limits and Possibilities of Legal Protection of Juveniles - Stevanović, Ivana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
There are different opinions on possibilities, legitimacy and limits of criminal protection of juveniles, but the answer to these questions, one or another solution, has very important consequences on society and the individual. The author approaches this problem through a brief overview of the ongoing review of the social and ethical foundation of criminal law in light of the limits of legal protection of juveniles, as well as through the questions of its legitimacy, because the possibilities of legal protection themselves are of certain importance for its legitimacy. For this reason, the legitimacy of the criminal protection of juveniles is associated with the principle of fairness and proportionality, without which the existence of the modern criminal law system is unimaginable today.